2017
DOI: 10.1177/1087054717725875
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parental Monitoring in Mediating the Link Between Adolescent ADHD Symptoms and Risk-Taking Behavior

Abstract: These findings suggest that parental knowledge is negatively affected by the presence of ADHD symptoms, and may in turn lead to risk-taking behavior. The findings emphasize the need to target parenting and in particular parental knowledge of the child's whereabouts to reduce risk-taking behaviors among youth with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 45 publications
6
19
1
Order By: Relevance
“…In three consecutive studies, we demonstrated that parental knowledge (i.e., "knowing where, how and with whom children spend their time" [13]) mediated the link between ADHD symptoms and different domains of impairment. In the first study, we replicated earlier findings on the mediating influence of parental knowledge on the link between ADHD symptoms and risk-taking behavior (RTB) [16]. Similar to the original study, parental knowledge mediated the association between ADHD symptoms and RTB.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In three consecutive studies, we demonstrated that parental knowledge (i.e., "knowing where, how and with whom children spend their time" [13]) mediated the link between ADHD symptoms and different domains of impairment. In the first study, we replicated earlier findings on the mediating influence of parental knowledge on the link between ADHD symptoms and risk-taking behavior (RTB) [16]. Similar to the original study, parental knowledge mediated the association between ADHD symptoms and RTB.…”
Section: Discussionsupporting
confidence: 80%
“…The current study relied on self-report only which might have caused biased (e.g., halo effects) or socially desirable answers. However, for the central construct of this study-parental knowledge-similar response patterns were observed for self-and other report [13], and previous work demonstrating similar results to the current study also relied on self-report [16]. The Resistance to Peer Influence scale (RPI) was specifically developed as a self-report scale with minimal influence of socially desirable responding [50].…”
Section: Strengths and Limitationssupporting
confidence: 63%
See 2 more Smart Citations
“…The significance of the indirect effects was tested via bootstrap analysis. If the 95% bias‐corrected confidence interval for the parameter estimate does not contain zero, mediation is demonstrated to have a statistically significant indirect effect (Pollak, Poni, Gershy, & Aran, ). The results of the Kolmogorov–Smirnov test suggest that our dependent variable may not be normally distributed.…”
Section: Methodsmentioning
confidence: 99%